Regulation of immune responses to infection through interaction between stem cell-derived exosomes and toll-like receptors mediated by microRNA cargoes - Moghaddam, Mehrdad Moosazadeh; Behzadi, Elham; Sedighian, Hamid; Goleij, Zoleikha; Kachuei, Reza; Heiat, Mohammad; Fooladi, Abbas Ali Imani (Frontiers in Cellular and Infection Microbiology, 2024)
Infectious diseases are among the factors that account for a significant proportion of disease-related deaths worldwide. The primary treatment approach to combat microbial infections is the use of antibiotics. However, the widespread use of these drugs over the past two decades has led to the emergence of resistant microbial species, making the control of microbial infections a serious challenge. One of the most important solutions in the field of combating infectious diseases is the regulation of the host’s defense system. Toll-like receptors (TLRs) play a crucial role in the first primary defense against pathogens by identifying harmful endogenous molecules released from dying cells and damaged tissues as well as invading microbial agents. Therefore, they play an important role in communicating and regulating innate and adaptive immunity. Of course, excessive activation of TLRs can lead to disruption of immune homeostasis and increase the risk of inflammatory reactions. Targeting TLR signaling pathways has emerged as a new therapeutic approach for infectious diseases based on host-directed therapy (HDT). In recent years, stem cell-derived exosomes have received significant attention as factors regulating the immune system. The regulation effects of exosomes on the immune system are based on the HDT strategy, which is due to their cargoes. In general, the mechanism of action of stem cell-derived exosomes in HDT is by regulating and modulating immunity, promoting tissue regeneration, and reducing host toxicity. One of their most important cargoes is microRNAs, which have been shown to play a significant role in regulating immunity through TLRs. This review investigates the therapeutic properties of stem cell-derived exosomes in combating infections through the interaction between exosomal microRNAs and Toll-like receptors.